PERAN KPU DALAM MENINGKATKAN PARTISIPASI POLITIK PEMILIH PEMULA PADA PEMILIHAN UMUM 2024 DI KABUPATEN LUWU TIMUR - Kamue, Yurni; Bakhtiar, Bakhtiar (Humano: Jurnal Penelitian, 2024)
The role of the KPU in increasing the political participation of novice voters is one of the tasks and functions of the KPU based on Law Number 7 of 2017 and explained in more detail in PKPU Number 5 of 2022. This study aims to determine the KPU's strategy in increasing the political participation of novice voters in East Luwu Regency. This type of research is qualitative research with a phenomenological approach. The type of data used is qualitative data with primary data sources and secondary data. Using data collection techniques, namely observation, interviews, documentation. Checking the validity of the data in this study using source triangulation with data analysis techniques consisting of data reduction, data presentation, and conclusion drawing. The results showed that the KPU strategy by providing electoral socialization and voter education can be said to be optimal and effective to increase the political participation of novice voters, this can be seen from the form of socialization carried out with various strategies, namely going directly to various high schools and campuses, watching together (Nobar) with novice voters, making democracy cafes in three sub-districts and carrying out various activities in the community such as election jingle gymnastics and so on.